2020
DOI: 10.1007/s11695-020-04672-4
|View full text |Cite
|
Sign up to set email alerts
|

Is Routine Preoperative Esophagogastroduodenoscopy Prior to Bariatric Surgery Mandatory? Systematic Review and Meta-analysis of 10,685 Patients

Abstract: Background This systematic review and meta-analysis searched, retrieved and synthesized the evidence as to whether preoperative esophagogastroduodenoscopy (p-EGD) should be routine before bariatric surgery (BS). Methods Databases searched for retrospective, prospective, and randomized (RCT) or quasi-RCT studies (01 January 2000–30 April 2019) of outcomes of routine p-EGD before BS. STROBE checklist assessed the quality of the studies. P-EGD findings were categorized: Group 0 (no abnormal findings); Group 1 (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(3 citation statements)
references
References 69 publications
0
2
0
1
Order By: Relevance
“…The importance and necessity of routine EGD prior BS is still a matter of debate. A systematic meta-analysis of 10,685 patients showed that in 82% EGD did not change the surgical plan and therefore questions its justification [ 8 ]. American guidelines recommend preoperative EGD only for symptomatic patients, while in Europe it is recommended for all bariatric patients [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…The importance and necessity of routine EGD prior BS is still a matter of debate. A systematic meta-analysis of 10,685 patients showed that in 82% EGD did not change the surgical plan and therefore questions its justification [ 8 ]. American guidelines recommend preoperative EGD only for symptomatic patients, while in Europe it is recommended for all bariatric patients [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…La EDA preoperatoria es fundamental como screening de lesiones premalignas, pero su realización es controversial 14 . Algunos autores han encontrado anormalidades en hasta 16% de los pacientes, cambiando la conducta quirúrgica final 15 . Sin embargo, otros plantean que solamente se identifican anormalidades inespecíficas, clínicamente irrelevantes y que podrían conllevar a tratamientos innecesarios 16 .…”
Section: Discussionunclassified
“…However, an increasing amount of evidence shows that HHR is inefficient in preventing the occurrence and development of GERD after LSG. [86][87][88] For patients with obesity, whether receiving LSG and routine preoperative endoscopy 78,89,90 and HHR are necessary requires additional prospective studies. The good news is that LSG with anti-reflux fundoplication emerges as a new valid option for patients with GERD.…”
Section: Revisional Surgeries For Complications Of Lsg Revisional Surgeries For Gerdmentioning
confidence: 99%